Assessment of IL‐1β, IL‐6, TNF‐α, IL‐8, and CCL 5 levels in newly diagnosed Saudi patients with rheumatoid arthritis. (24th June 2022) - Alturaiki, Wael; Alhamad, Abdulaziz; Alturaiqy, Muath; Mir, Shabir Ahmad; Iqbal, Danish; Bin Dukhyil, Abdul Aziz; Alaidarous, Mohammed; Alshehri, Bader; Alsagaby, Suliman A; Almalki, Sami G.; Alghofaili, Fayez; Choudhary, Ranjay K.; et al.
Abstract: Background: Rheumatoid arthritis (RA) is a chronic systemic inflammatory disorder which mainly affects small joints, occurs most commonly in middle‐aged adults, and can be fatal in severe cases. The exact etiology of RA remains unknown. However, uncontrolled expression of pro‐inflammatory cytokines and chemokines can contribute to the pathogenesis of RA. Aim: In the current study, we assessed the potential of serum concentrations of interleukin (IL)‐1β, IL‐6, tumor necrosis factor (TNF)‐α, IL‐8, and C‐C motif chemokine ligand (CCL)5 as early predictive markers for RA. Methods: In addition to clinical examination, blood samples were collected from 100 Saudi patients recently diagnosed with early RA for basic and serological tests, including rheumatoid factor (RF), C‐reactive protein (CRP), and erythrocyte sedimentation rate (ESR). Sera of 32 healthy individuals were used as controls. Specific enzyme‐linked immunosorbent assay was used to quantify the serum IL ‐ 1β, IL‐6, TNF‐α, IL‐8, and CCL5 levels in the samples. Results: Our results indicated that RF, CRP, and ESR levels were higher in RA patients compared to controls. Furthermore, serum levels of IL ‐ 1β, IL‐6, IL‐8, and CCL5, but not TNF‐α, significantly increased in RA patients compared to controls. Conclusion: Overall, the findings suggested that IL‐1β, IL‐6, IL‐8, and CCL5 can be used as biomarkers in the early diagnosis of RA.